Stability influence of weak interlayer rock slope under rainfall - Zhang, Shuhui; Zhu, Guangpei; Xu, Chong; Ma, Junxue; Sun, Zhiyuan (Frontiers in Earth Science, 2025)
In this study, we investigate the stability of soft rock slopes with weak interlayers under rainfall through indoor model tests and numerical simulations, focusing on a slope in northeast China. Weak interlayers, characterized by low thickness and mechanical strength compared to adjacent rock masses, are prone to water-induced softening, threatening slope stability. Key findings reveal the following: 1) rainfall triggers sliding along weak interlayers, accumulating debris at slope toes. Prolonged infiltration reduces rock–soil friction, potentially extending failure zones through slightly weathered tuff; 2) Non-rainfall scenarios induce slope failures primarily at crests and shoulders, whereas rainfall shifts the maximum displacement to the slope feet; 3) Expanding plastic zones under intensified rainfall indicate progressive instability development toward deeper slope surfaces. The results demonstrate rainfall’s critical role in altering failure mechanisms and depth, providing insights for risk mitigation in geotechnical projects involving weak interlayers.